A Review on Key Considerations of Mass Gathering Management: Lesson Identified Lesson Learnt - Nik Arif, Nik Mohamad; Azizul Fadzli, Wan Jusoh@Ab Rahim; Nik Ahmad Shaiffudin, Nik Him (2018)
Introduction: Mass gatherings, including scheduled events in sports facilities, air shows, rock concerts, outdoor celebrations, and visits by dignitaries, vary in their complexity and demand for medical services. Material and Methods: This review aims to analyses previous cases of disaster at mass gathering events, documenting the lessons identified, to provide considerations when planning for future events. A literature search was carried out using Medline, Cochrane, and Embase. A free-text search was also conducted using Google to link mass gathering events to disaster incidents in order to widen the search beyond peer-reviewed publications. All peer-review literature articles found containing information pertaining to lessons identified from mass gathering crowd disasters were analysed and reviewed. Result: 21 reported mass gathering incidents have been reviewed, analysed and abstracted. Main learning points is categorized into 4 key areas for discussion; A. Medical Preparedness, B. Emergency Response, C. Psychosocial consideration and D. Overcrowding and Crowd Control Discussions: Analysis of previous crowd disasters indicates a need for early detailed planning of crowd policies, evacuation procedures and involvement of emergency services which are necessary to promote and provide a successful event. Further studies of mass gathering events are warranted to advance not only the epidemiological knowledge base, but also to gain further lessons of emergency preparedness and response. Conclusion: Generic themes from disasters at mass gathering events emerge from this collection of literature. The key consideration in medical preparedness and emergency responses are overcrowding and crowd control, and early identification and management of psychosocial complication